Original Research The Effect of Yoga or Nonpharmacotherapy on Dysmenorrhore in Medical Students of Andalas University, Indonesia - Rifqah Wardah Astarini; Muhammad Zulfadli Syahrul; Mustafa Nour; Beni Indra; Aladin Aladin; Miftah Irramah (Jurnal sosial dan sains, 2024)
Background: Dysmenorrhea is a menstrual pain that is often experienced by young women, with a global prevalence of 16.8-81%. In Indonesia, the prevalence reaches 54.89%, with adolescent girls being the largest group. Treatment generally uses analgesics, but it has side effects. Yoga as a non-pharmacological therapy can reduce pain through muscle relaxation. Purpose: Analyzing the effect of yoga therapy on the intensity of the degree of dysmenorrhea in female students of the Class of 2018 Undergraduate Medical Education Study Program, Faculty of Medicine, Andalas University. Methods: This research uses a pure experimental design with a pre-test, post-test, and only group design, with a sample size of 32 people. The research instrument used in the study was a pre-test and post-test questionnaire, which contained VAS scores and guidelines regarding yoga movements. The questionnaire contains a Visual Analog Scale (VAS), which consists of a vertical scale from 0 to 10 cm. Results:  The results showed there were no differences related to age. As many as 18% of respondents usually took analgesics, while 81.3% did not take analgesics to treat dysmenorrhea before yoga therapy. Meanwhile, after yoga therapy, 5 out of 6 respondents who usually consumed analgesics in previous menstrual cycles no longer consumed analgesics, and one respondent still consumed analgesics. Bivariate analysis showed a value of p=0.00 (p<0.05), which means there is a relationship between the provision of yoga therapy and the degree of dysmenorrhea. Where providing yoga therapy can reduce the intensity of pain in respondents who experience dysmenorrhea. Conclusion: This research concludes that there is a significant relationship between the provision of yoga therapy and the degree of dysmenorrhea.